A Fully Integrated VCO at 2GHz - Zannoth, Markus; Kolb, Bernd; Fenk, Josef; Weigel, Robert (IEEE International Solid-State Circuits Conference, 1998)
An integrated voltage-controlled oscillator (VCO) at a frequency of 2 GHz is implemented in a f/sub T/= 25 GHz standard bipolar process. The phase noise of the VCO is -136 dBc/Hz at 4.7 MHz frequency offset. The LC-resonator uses vertically coupled on-chip inductors and integrated tuning diodes. Due to the poor performance of integrated resonators on silicon ICs, oscillators with phase noise meeting requirements of wireless applications are difficult to integrate. With fully integrated designs only the standards for cordless phones, for instance DECT, can be achieved. The critical point in the DECT-specification is the emission of the transmitter due to intermodulation in the third adjacent channel, that must be <-47 dBm. This value is measured with an integration bandwidth of 1 MHz centered at the nominal center frequency. With a channel-spacing of 1.728 MHz the third adjacent channel is located 5.184 MHz from the actual transmit channel frequency. The beginning of the integration bandwidth is at an offset frequency of 4.684 MHz related to the nominal frequency of the transmit channel. This is the offset frequency, at which the specification must be met. The resulting noise requirement is -132 dBc/Hz at a offset frequency of 4.684 MHz, when the integration bandwidth and the transmit output power of 25 dBm are taken into account.
elib2cris::1512001600,zannoth1998a